Activity of speaking skills of grade V students with the help of a paired storytelling model on the theme of the environment of SDN Tegalasri 4 - Oktaviarini, Nourma; Astutik, Leny Suryaning (Jurnal Bidang Pendidikan Dasar, 2024)
The research aims to analyze and describe the implementation of the learning process of speaking skills by using paired storytelling learning model for fifth grade students of SDN Tegalasri 4. The research method used in this research is qualitative research. The subjects in this study were fifth grade students of SDN Tegalasri 4. Data collection techniques used interviews, observation, and documentation. The results of the learning implementation research using the paired storytelling learning model obtained a scoreÂ  84% "very good". The results of the observation of students' speaking skills using the paired storytelling learning model obtained a scoreÂ  71% "good". The conclusion of this research is that learning speaking skills using paired storytelling can motivate to learn better in improving students' speaking skills in class V SDN Tegalasri 4.